Molecular Epidemiology, Natural History, and Long-Term Outcomes of Multidrug-Resistant Enterobacterales Colonization and Infections Among Solid Organ Transplant Recipients. (10th May 2021) - Hong Nguyen, M; Shields, Ryan K; Chen, Liang; William Pasculle, A; Hao, Binghua; Cheng, Shaoji; Sun, Jonathan; Kline, Ellen G; Kreiswirth, Barry N; Clancy, Cornelius J
Abstract: Background: Multidrug-resistant Enterobacterales (MDR-E), including carbapenem-resistant and third-generation cephalosporin-resistant Enterobacterales (CRE, CefR-E), are major pathogens following solid organ transplantation (SOT). Methods: We prospectively studied patients who underwent lung, liver, and small bowel transplant from February 2015 through March 2017. Weekly perirectal swabs (up to 100 days post-transplant) were cultured for MDR-E. Whole-genome sequencing (WGS) was performed on gastrointestinal (GI) tract–colonizing and disease-causing isolates. Results: Twenty-five percent (40 of 162) of patients were MDR-E GI-colonized. Klebsiella pneumoniae was the most common CRE and CefR-E. Klebsiella pneumoniae carbapenemases and CTX-M were leading causes of CR and CefR, respectively. Thirty-five percent of GI colonizers developed MDR-E infection vs 2% of noncolonizers ( P < .0001). The attack rate was higher among CRE colonizers than CefR-E colonizers (53% vs 21%, P = .049). GI colonization and high body mass index were independent risk factors for MDR-E infection ( P ≤ .004). Thirty-day mortality among infected patients was 6%. However, 44% of survivors developed recurrent infections; 43% of recurrences were late (285 days to 3.9 years after the initial infection). Long-term survival (median, 4.3 years post-transplant) did not differ significantly between MDR-E–infected and MDR-E–noninfected patients (71% vs 77%, P = .56). WGS phylogenetic analyses revealed that infections were caused by GI-colonizing strains and suggested unrecognized transmission of novel clonal group-258 sublineage CR- K. pneumoniae and horizontal transfer of resistance genes. Conclusions: MDR-E GI colonization was common following SOT and predisposed patients to infections by colonizing strains. MDR-E infections were associated with low short- and long-term mortality, but recurrences were frequent and often occurred years after initial infections. Findings provide support for MDR-E surveillance in our SOT program. Abstract : Twenty-five percent of transplant recipients were gastrointestinally colonized by multidrug-resistant Enterobacterales, which predisposed to invasive infections. Infections were associated with low short-term and long-term mortality, but recurrences were common for years. Whole-genome phylogenetic analyses linked infections to colonizing strains.